2020
DOI: 10.34172/ps.2019.59
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antioxidant Activities of Novel Marine Bacteria (Bacillus 2011SOCCUF3) Isolated from Marine Sponge (Spongia officinalis)

Abstract: Background: Bacillus species represent a rich source of new bioactive metabolites that can combat diseases. Methods: Bacillus strain was isolated from the marine sponge Spongia officinalis and routinely maintained on marine broth. The bacteria strain was identified as Bacillus 2011SOCCUF3 using 16S rDNA sequencing. The strain was cultured on Tryptone Casein Oat Soluble Starch (TCOATSS) media with continuous agitation for 4 days. The fermented broth was centrifuged, and the supernatant was mixed with 10% (w/v) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The antibacterial activity against MDR bacteria belonged to the members of the Bacillus genus. Previous studies on bacteria associated with Spongia have shown similar results (Odekina et al 2020). According to Mondol et al (2013) Bacillus isolated from the sea produces secondary metabolites various antimicrobial activities (Mondol et al 2013).…”
Section: Phylogenetic Analysesmentioning
confidence: 61%
“…The antibacterial activity against MDR bacteria belonged to the members of the Bacillus genus. Previous studies on bacteria associated with Spongia have shown similar results (Odekina et al 2020). According to Mondol et al (2013) Bacillus isolated from the sea produces secondary metabolites various antimicrobial activities (Mondol et al 2013).…”
Section: Phylogenetic Analysesmentioning
confidence: 61%
“…The extract of the former strain was efficient against Bacillus subtilis, E. coli, S. aureus, Agrobacterium tumefaciens and the yeast Saccharomyces cerevisiae; while the extract of the latter strain demonstrated activity against B. subtilis, A. tumefaciens, S. aureus and the yeast S. cerevisiae [87]. Frequently, the isolated bacterial species belong to the genus Bacillus, as is the case for the strain "2011SOC-CUF3", isolated from the marine sponge Spongia officinales (Linnaeus, 1759), subfractions of which were active against as S. aureus (MIC = 247 µg/mL), S. tiphy (MIC = 83 µg/mL), P. aeruginosa (MIC = 162 µg/mL) and E. coli (628 µg/mL), compared with the positive controls (ciprofloxacin and fluconazole) [88]. Similarly, from the sponge Halichondria glabrata (Keller, 1891) (collected in Mumbai) the strain GSA10 was isolated and successively classified for its similarities with pG1 Bacillus amyloliquefaciens.…”
Section: Antibacterial and Antiviral Activitiesmentioning
confidence: 96%
“…(2011SOCCUF3), isolated from Spongia officinalis (Linnaeus, 1759), showed a strong antifungal activity. The vacuum liquid chromatography (VLC) fractions obtained from this bacterium showed specific activity against C. albicans (MIC = 108 µg/mL) [88]. Similarly, against C. albicans, a methanol extract from the marine Demospongia Neopetrosia exigua (Kirkpatrick, 1900) showed encouraging activity [77], as well as for the "peptide C" extracted from the deep sea marine sponge S. fortis (MIC = 18.07 µM [81].…”
Section: Other Miscellaneous Activitiesmentioning
confidence: 99%
“…Briefly, the dried extract (10.8 g) was triturated with silica gel (10.0 g) in a mortar and loaded onto a sintered glass Buckner funnel (6 cm x 30 cm, ID) attached to a vacuum line and packed with graded silica gel 60 (0.04-0.063 mm, 230-400 mesh) as adsorbent, then eluted with methanol in acetone gradient (25, 50, 75 and 100%, 1 L each) to yield the VLC fractions (F1-F4). These sub-fractions were subsequently concentrated to remove the solvents and used for the antimicrobial and antioxidant studies 13 .…”
Section: Extraction and Purification Proceduresmentioning
confidence: 99%